ANALISIS ELEMEN BERITA HOAKS DI WEBSITE - Tyas Oktaviana; Nurul Hasfi (Interaksi Online, 2020)
This research is motivated by the emergence of problems in the community due to the impact of the spread of hoax on the internet. The massive spread of hoax on the internet is sourced from unofficial or fake websites that present as if they are trusted online news portals through presenting various news information. The low interest in reading and media literacy in Indonesian society makes it easy for people to trust sensational or horrendous news without verifying the truth of the news. This study aims to identify how the news elements of news hoax are engineered and to identify what types of news hoax often appear. This research is a mixed method with descriptive quantitative text analysis. To answer this research question, researchers used the concept of online journalism and hoax. The results of the study found that the news elements that experienced manipulation in the text composition + supplementary data category were in the title section. Hoax are changed to provocative sentences by taking the names of figures, institutions / organizations and countries. While the category of news elements that have been manipulated in the news element is what by replacing or adding sentences that match the news hoax. The type of hoax that often appears on websites is a type of disinformation with manipulated content categories.